Accounting Regulations in Poland: Do They Work or Should They Be Improved? A Survey Among Accountants and Other Professionals - Marek CIESLAK (Communications of International Proceedings, 2024)
The aim of the study was to find out the opinions of accountants, people professionally involved in finance, managers of business units and working in other departments of business units on the accounting regulations in force in Poland. A large part of the regulations governing broadly understood accounting is introduced at the international level, and those introduced at the national level are often inspired by international solutions. It is not possible to consult them widely with the community, so getting to know the opinions of the people they concern becomes particularly important. The study was conducted in the form of an anonymous survey. The results of the survey indicate that the majority of those involved directly or indirectly in accounting believe that accounting needs improvement. A very small proportion of respondents felt that accounting does not need improvement. Accounting regulations are perceived as ambiguous, allowing for arbitrary decisions, and unfortunately perceived as not good due to little convergence with tax regulations. Respondents also noted the problem of falsification of financial statements, indicating that they had encountered or heard of falsification of accounts. At the same time, an equally large group of respondents considers financial statements to be as reliable as necessary.
Keywords: accounting regulation; quality of financial statements; improvement; survey; Poland